Probing starch–iodine interaction by atomic force microscopy. Issue 4 (11th December 2013) - Du, Xiongwei; An, Hongjie; Liu, Zhongdong; Yang, Hongshun; Wei, Lijuan
Summary We explored the interaction of iodine with three crystalline type starches, corn, potato, and sweet potato starches using atomic force microscopy. Results revealed that starch molecules aggregated through interaction with iodine solution as well as iodine vapor. Detailed fine structures such as networks, chains, and super‐helical structures were found in iodide solution tests. The nanostructures formed due to iodine adsorption could help to understand the formation and properties of the starch–iodine complex. SCANNING 36:394–400, 2014. © 2013 Wiley Periodicals, Inc.